Role of Immune Microenvironmental Factors for Improving the IPI-related Risk Stratification of Aggressive B Cell Lymphoma - GONG, Yi; CHEN, Rui; ZHANG, Xi; ZOU, Zhong Min; CHEN, Xing Hua (Biomedical and environmental sciences, 2017)
Objective To investigate the risk stratification of aggressive B cell lymphoma using the immune microenvironment and clinical factors. Methods A total of 127 patients with aggressive B cell lymphoma between 2014 and 2015 were enrolled in this study. CD4, Foxp3, CDS, CD68, CD163, PD-1, and PD-L1 expression levels were evaluated in paraffin-embedded lymphoma tissues to identify their roles in the risk stratification. Eleven factors were identified for further evaluation using analysis of variance, chi-square, and multinomial logistic regression analysis. Results Significant differences in 11 factors （age, Ann Arbor stage, B symptom, ECOG performance status, infiltrating CD8＋ T cells, PD-L1 expression, absolute blood monocyte count, serum lactate dehydrogenase, serum iron, serum albumin, and serum l~2-microglobulin） were observed among patient groups stratified by at least two risk stratification methods [International Prognostic Index （IPI）, revised IPI, and NCCN-IPI models] （P 〈 0.05）. Concordance rates were high （81.4%-100.0%） when these factors were used for the risk stratification. No difference in the risk stratification results was observed with or without the Ann Arbor stage data. Conclusion We developed a convenient and inexpensive tool for use in risk stratification of aggressive B cell lymphomas, although further studies on the role of immune microenvironmental factors are needed.